PENINGKATAN LITERASI SISWA SEKOLAH DASAR DENGAN MENGGUNAKAN STRATEGI VOCABULARY IN THE CLOUDS - Eka Fanti Sulistiyaningsih; Etika Dewi Kusumaingtyas; Endang Susilowati; Tiara Nurwanti (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2023)
Background: Literacy is an ability that is really needed by a person. Literacy is the basis for a person to develop their abilities, apart from that, in terms of receiving new information, literacy has a major role. This makes the government promote literacy improvement programs from an early age. In particular, the implementation of literacy programs is often found at the elementary and middle school levels. Apart from that, equal distribution of literacy skills in Indonesia is also very important in improving human resources in this country. This is proven when the literacy skills between students who attend schools located in big cities and the literacy skills of students who go to schools in fairly underdeveloped areas have quite significant differences, therefore there is a need for programs which can reach the average Indonesian community. in terms of increasing literacy for future generations.   Methodology: The target of this activity is students at SD Negeri 4 Juworo. The stages of implementing the activity include observation and discussion with teachers at SD Negeri 4 Juworo. Observations are carried out to identify the condition of partners implementing activities and selecting programs for implementing activities. The observation results show that the literacy skills of SD Negeri 4 Juworo students are still low. So, the An Nuur University service team implemented the use of the vocabulary in the clouds strategy in the classroom when literacy learning was carried out. The form of implementation of this strategy is in the form of games that involve the students actively in the classroom.   Results: After the coloring competition activity, fine motoric development in preschool children increased.   Conclusion: Parents' knowledge about fine motor development increases, children can carry out tasks well, children's willingness to color contributes to fine motor development in preschool children.